We have the following equation:
2x2 - 6x + 7 = 0
Using the resolver we have:
x = (- b +/- root (b ^ 2 - 4 * a * c)) / (2 * a)
Substituting values we have:
x = (- (- 6) +/- root ((- 6) ^ 2 - 4 * 2 * 7)) / (2 * 2)
Rewriting we have:
x = (6 +/- root (36 - 56)) / (4)
x = (6 +/- root (-20)) / (4)
x = (6 +/- root (-4 * 5)) / (4)
x = (6 +/- 2raiz (-5)) / (4)
x = (6 +/- 2raiz (-1 * 5)) / (4)
x = (6 +/- 2raiz (5) * i) / (4)
x = (3 +/- root (5) * i) / (2)
The solutions are:
x1 = (3 + root (5) * i) / (2)
x2 = (3 - root (5) * i) / (2)
Answer:
x1 = (3 + root (5) * i) / (2)
x2 = (3 - root (5) * i) / (2)